Kendala Guru dalam Pembelajaran Matematika Secara Daring pada Masa Pandemi Covid-19 di MIN 6 Banda Aceh - Hayati, Zikra (Ibtida'i, 2022)
The existence of covid-19 has made face-to-face learning switch to online learning, this is done to reduce the spread of covid-19. However, the effect on education causes mathematics learning carried out by online teachers to be less effective than offline mathematics learning. Therefore, this study aims to find out what obstacles are faced by teachers in online mathematics learning during the covid-19 pandemic at MIN 6 Banda Aceh, as well as solutions to these obstacles. This research uses descriptive qualitative. The research subjects were mathematics teachers in grades IV-1, IV-5, V-1, V-5, VI-5, and VI-2. Data collection techniques using interviews, questionnaires, and documentation. The data analysis technique is data reduction, data presentation, conclusion drawing, and verification. Based on the results of the questionnaire Most (83%) teachers often have problems when conveying mathematical concepts to students in online learning, more than half (67%) teachers have problems using the question and answer method in online learning, much than half (67%) teachers constrained by advertisements and notifications on mobile phones/laptops interfering with online learning, more than half (67%) of teachers are constrained by students not being enthusiastic in participating in online learning, Most teachers and students do not focus on online learning (67%), more than half ( 67%) teachers are constrained when students are constrained because they do not have cellphones/gadgets when learning online.